The concept of and design strategy for decision support systems - Abdul Barri Md Mokhtar (Penerbit Universiti Kebangsaan Malaysia, 1984)
Decision Support Systems (DSS) ha e become an increasinglyimportant type of computer-based information system.Unlike Electronic Data Processing (EDP) or Management Information Systems (MIS), DSSspecifically oriented toward the kind of information processing activitiesthat constitute a decision process. It serves to increase the effectiveness of the managers in making decisions pertaining to the management of an organization. This article begins by examining the concepts of DSS, focusing on the various definitions given in the literature so that a unified view of what DSS really is and how it different form other computer-based information system, can be formulated. The paper then discussesbriefly the hardware and software are requirements of DSS. Following this, a generic framework for designing DSS is presented. Finally, the strategies for designing DSS are proposed and discussed. The paper argues that the appropriate strategy depend on the objective and decision situationparticular DSS is meant of support.